Comparative analysis of organisational performance using the EFQM Excellence Model: the sustainability perspective - Fleaca, Cristina-Mihaela; Severin, Irina (Cognitive Sustainability, 2024)
Given the escalating environmental challenges, it is imperative for companies to recognize the impact of their activities on the planet. By acknowledging their environmental responsibilities, organizations can develop practices and foster cultures that minimize waste and enhance value while optimizing costs and save time, thereby improving productivity. Therefore, global organizations have prioritized sustainable business practices that safeguard the environment, economy, and society. Thus, this paper seeks to conduct an in-depth analysis of the sustainability strategies employed by companies within the energy sector. To achieve a comprehensive evaluation, the study utilizes the EFQM Excellence Model criteria as a wide framework. This model provides a structured and systematic approach to examining and guiding the sustainability practices of these organizations, ensuring a thorough and detailed assessment of their efforts and outcomes. This approach aims to identify and present best practices and common pitfalls in terms of sustainability through comparative analysis. It will highlight key aspects that each analyzed organization employs to enhance organizational performance from a sustainability perspective. Through this process, a complete collection of examples will be compiled, showcasing both effective practices and common pitfalls in sustainability. These examples will function as a resource for businesses, helping them to improve their organizational performance in the field of sustainability. By learning from these case studies, organizations can adopt successful strategies and avoid common mistakes, ultimately fostering a more sustainable and efficient business environment.